Ancient Schwannoma of the Hard Palate Accompanied by Hyponatremia: A Unique Case Report : Hard Palate Schwannoma with Hyponatremia - Nikafshar, Nima; Masoudi, Mojde; Vadaye Kheiri, Siavash; Johari, Maryam (Regeneration, Reconstruction & Restoration (Triple R), 2025)
Schwannoma is a benign neurogenic neoplasm originating from the Schwann cells within the peripheral nervous system. Its incidence is documented at about 25-45%, yet its occurrence in the oral cavity is less than 12%. Given that neurogenic neoplasms are a well-documented but uncommon reason for hyponatremia, this is a case report of an ancient schwannoma of the palate, perforating the nasal floor, in an 80-year-old female, along with hyponatremia. An 80-year-old female presented with painful swelling in the anterior maxilla and the nasal floor. She had a history of hyponatremia, high blood pressure, tachycardia, and hypothyroidism. Clinical examination revealed apparent swelling in the buccal vestibule and the midline of the hard palate; the lesion had perforated the palate to the nasal cavity. cone beam computed tomography revealed swelling of the soft tissue and erosion of the underlying bone. An excisional biopsy surgery was performed by laser. Microscopic examination showed spindle cell neoplasm composed of cellular areas (Antoni A), nuclear palisading (verocay bodies), and pauci-cellular microcystic areas (Antoni B). Some tumoral cells showed nuclear atypia including nuclear enlargement with hyperchromasia with irregular border. Given that, the definitive diagnosis was an ancient Schwannoma. The present case is a unique type of schwannoma, placed in an uncommon location. It presented pain and, more importantly, perforated the hard palate to the nasal cavity.